2002
DOI: 10.1016/s0928-8244(01)00303-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential virulence and antimicrobial susceptibility of Aeromonas popoffii recovered from freshwater and seawater

Abstract: Aeromonas popoffii is the most recent species within the genus Aeromonas described from freshwater. In our study this species was also recovered from this habitat and for the first time from seawater. Most of the virulence factors known in Aeromonas spp. (aerolysin/hemolysin, serine protease, lipases and DNases) were highly prevalent in this species. Third-generation cephalosporins and quinolones were the most active antimicrobial agents against A. popoffii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 28 publications
1
27
1
5
Order By: Relevance
“…All presumptive Aeromonas isolates were first screened using Aeromonas-genus-specific primers targeting the glycerophospholipid cholesterol acyltransferase gene (gcat) using the reaction and cycling conditions described by Soler et al (2002); they were then identified at the species level based on the sequencing analysis of 2 housekeeping genes, rpoD and gyrB. An approximately 1100 bp fragment of gyrB and a 820 bp fragment of rpoD were amplified from the template DNA, purified using the FastGene Gel/PCR extraction kit (Nippon Genetics) and sequenced using the BigDye Terminator V3.1 Cycle Sequencing Kit on the 3130xl Genetic Analyzer (Applied Biosystems).…”
Section: Dna Extraction and Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…All presumptive Aeromonas isolates were first screened using Aeromonas-genus-specific primers targeting the glycerophospholipid cholesterol acyltransferase gene (gcat) using the reaction and cycling conditions described by Soler et al (2002); they were then identified at the species level based on the sequencing analysis of 2 housekeeping genes, rpoD and gyrB. An approximately 1100 bp fragment of gyrB and a 820 bp fragment of rpoD were amplified from the template DNA, purified using the FastGene Gel/PCR extraction kit (Nippon Genetics) and sequenced using the BigDye Terminator V3.1 Cycle Sequencing Kit on the 3130xl Genetic Analyzer (Applied Biosystems).…”
Section: Dna Extraction and Molecular Identificationmentioning
confidence: 99%
“…All the isolates were screened by PCR for the presence of 7 genomic markers potentially linked to virulence -aerolysin (aerA), cytotoxic enterotoxin (act), the heat-stable and heat-labile cytotonic enterotoxins (ast and alt, respectively), serine protease (ser), DNase (exu) and flagellin (fla) -using the primers and conditions described by Nawaz et al (2010) and Soler et al (2002). The sequence of each primer used to amplify the target genes, the expected size of the PCR products and their references are listed in Table S3 in the Supplement.…”
Section: Detection Of Virulence-related Genes By Pcrmentioning
confidence: 99%
“…Although most 16S rRNA gene sequence-derived relationships have correlated well with the DNA homology groups (HG), difficulties have been encountered in splitting closely related species (MartĂ­nez-Murcia, 1999;MartĂ­nez-Murcia et al, 2005). DNA probes and restriction fragment length polymorphism (RFLP) profiles designed from 16S rRNA gene diagnostic regions have served to identify Aeromonas at the species level (Ash et al, 1993a, b;Borrell et al, 1997;Dorsch et al, 1994;Figueras et al, 2000;Khan & Cerniglia, 1997;Lee et al, 2002;Soler et al, 2002). Recent sequencing analyses based on the gene sequences of gyrB (encoding the B subunit of DNA gyrase, a type II DNA topoisomerase) and rpoD (encoding the s 70 factor, one of the sigma factors that confers promoter-specific transcription initiation on RNA polymerase) have demonstrated that they are excellent molecular markers for phylogenetic inference in the genus Aeromonas (Soler et al, 2004;Yåñez et al, 2003) and these chronometers seem to be well synchronized.…”
mentioning
confidence: 99%
“…However, this bacterium is able to produce some virulence factors, conferring a pathogenic role. These genes were present in all A. popoffii strains studied by Soler et al (11,12). For the isolate described here, we demonstrated the presence of genes coding for aerolysin/hemolysin and serine protease.…”
mentioning
confidence: 82%